Vocasia's Marketing Communication Strategy in Increasing the Number of Customers - Yuniansri, Xena Raihan; Setyawan, Sidiq (Universitas Muhammadiyah Surakarta, 2022)
Purpose: This study aims to gain a practical and theoretical understanding of how to use new media as a means of promotion for Vocasia start-ups in increasing the number of customers by testing 4 elements of the Innovation Diffusion theory (innovation, communication channels, timeframe, and social). Methodology: Researchers use qualitative research methods with a case study approach and data collection techniques from observation, documentation, and in-depth interviews. Results: The results of the study show that the adoption of technological innovations in promotional strategies through new media, especially in the use of social media platforms such as Instagram, WhatsApp, TikTok, and Blogs with various promotional offers can be an attraction for customers to make purchases while successfully increasing the number of Vocasia customers. Applications/Originality/Value: This research focuses on marketing communication strategies in increasing the number of customers implemented by Vocasia as a Start-up company in the form of a learning management system platform as well as an online educational marketplace that provides improvement services and skills in the field of self-development. In its marketing, Vocasia uses social media as the main marketing medium. This research is expected to be used as a source of information as well as consideration for people in the business industry, especially in the field of start-ups in increasing the number of customers by implementing promotions using appropriate and effective new media.